Programmable Origami Strings. Issue 3 (22nd January 2018) - Kamrava, Soroush; Mousanezhad, Davood; Felton, Samuel M.; Vaziri, Ashkan
Abstract: Origami‐inspired mechanisms have demonstrated a variety of beneficial features including geometric complexity and structural resilience. However, a limited number of studies have focused on their programmability in kinetics and kinematics through rearranging the folding pattern. In this paper, an origami "string, " a slender structure with a programmable trajectory, is presented. The string is composed of a number of elements that can be individually programed to achieve a specific folding pattern and curvature. The mechanism has a single degree of freedom, allowing it to be actuated from one end while maintaining precise positioning along the entire string length. The relationship between the fold pattern and string path is simulated and experimentally validated, and its application as a robotic gripper and a biomimetic hand is demonstrated. These results demonstrate the capabilities of the proposed origami strings in accomplishing precise positioning and programed shape and function. Abstract : A programmable origami string is a single degree of freedom mechanism which folds from a flat to a programmed 3D configuration. The string design is inspired by origami while paper and creases are replaced with 3D printed panels and hinges, respectively. The string folding can be fully controlled using a single actuator as demonstrated for a potential robotic application, see image.